2020
DOI: 10.1136/medethics-2019-105989
|View full text |Cite
|
Sign up to set email alerts
|

Design thinking in medical ethics education

Abstract: BackgroundDesign thinking (DT) is a tool for generating and exploring ideas from multiple stakeholders. We used DT principles to introduce students to the ethical implications of organ transplantation. Students applied DT principles to propose solutions to maximise social justice in liver transplant allocation.MethodsA 150 min interactive workshop was integrated into the longitudinal ethics curriculum. Following a group didactic on challenges of organ donation in the USA supplemented by patient stories, teams … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…As of June 2023, this represents the first known application of the design‐thinking process to address candidate selection in graduate medical education. Prior applications of design thinking in medical education include development of tools for care transitions, virtual health training, procedural simulations, and well‐being initiatives ( 10 , 11 , 12 , 13 , 14 , 15 ). Because interviews are, by their nature, human‐centered, it was a natural decision to use such a quality improvement framework to better characterize the interview process and to identify areas for improvement.…”
Section: Discussionmentioning
confidence: 99%
“…As of June 2023, this represents the first known application of the design‐thinking process to address candidate selection in graduate medical education. Prior applications of design thinking in medical education include development of tools for care transitions, virtual health training, procedural simulations, and well‐being initiatives ( 10 , 11 , 12 , 13 , 14 , 15 ). Because interviews are, by their nature, human‐centered, it was a natural decision to use such a quality improvement framework to better characterize the interview process and to identify areas for improvement.…”
Section: Discussionmentioning
confidence: 99%
“…We have found that this approach not only increases the implementation of design thinking but also highlights the adaptable use of design thinking skills across different curricular themes. For example, design thinking has been successfully integrated into medical student ethics teaching about organ transplantation 27 and interprofessional learning about aging and disability. 28…”
Section: Recommendations For Using Design Thinking In Medical Educationmentioning
confidence: 99%
“…Medical ethics and humanities always are essential education for students to being a specialist in medicine, because professionalism is indispensable with scienti c, ethical and social 1,2 . Surely, medical students "must" include education regarding humanities theory and behavior in every medical college around the world 3 . Yet, discouragingly, it is often contradictory to combine medical professional knowledge with humanistic education within a limited learning time, along with the increase of learning tasks in many academic disciplines 4,5 .…”
Section: Introductionmentioning
confidence: 99%